Perlindungan Hak Waris Anak yang Lahir dari Perkawinan Tidak Tercatat Menurut Kompilasi Hukum Islam - Adjani, Muhammad Ahnaf; Yani, Encep Ahmad (Universitas Muhammadiyah Ponorogo, 2025)
This study examines the protection of inheritance rights of children born from unregistered marriages according to the Compilation of Islamic Law (KHI) using descriptive qualitative methods and a normative legal approach. The purpose of the study is to describe in detail the facts on the ground while analyzing applicable legal norms and their conformity with community practices. Data collection techniques were carried out through a literature study including books, journals, articles, laws and regulations, and relevant documents, which were then critically analyzed to produce a comprehensive understanding. The results show that unregistered marital status has a significant impact on the legal recognition of children as heirs. According to the KHI, children are the primary heirs, but this provision only applies to children born from legal and officially registered marriages. Children born outside of registered marriages generally do not receive inheritance rights from their biological fathers, unless there is legal recognition or a court decision. In practice, the protection of children's inheritance rights is often hampered by patriarchal culture, low legal literacy, and differences between customary law and Islamic law. Daughters, children born out of wedlock, and adopted children tend to be more disadvantaged in inheritance distribution. As a solution, marriage confirmation at the Religious Court is the primary step in legalizing marital status, thereby granting children legal status as heirs. Another alternative is to adhere to Constitutional Court Decision No. 46/PUU-VIII/2010, which allows illegitimate children to inherit from their biological father with proof of a civil relationship. Increasing public legal awareness and facilitating access to marriage registration are key to ensuring fair protection of children's inheritance rights in accordance with Islamic principles of justice and national law.